2019
DOI: 10.18203/2349-2902.isj20192280
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in low socioeconomic patients with severe acute pancreatitis treated either with early nasogastric tube or total parenteral nutrition: a randomized controlled trial

Abstract: Background: Early nasogastric feeding has shown beneficial effect in the low socioeconomic group of patient with severe acute pancreatitis (SAP). The current randomized controlled study was performed to assess the effect of early nasogastric feeding as compared to total parenteral nutrition (TPN).Methods: Fifty patients admitted with diagnosis of SAP were randomly allocated to receive nnteral feeding (EF) (at the rate of 25 ml/hour and was gradually increased up to 100 ml/hr) or TPN within 24 hours of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…20 However, Kumar et al in their study, similar to current study reported a dominance of gall stone disease (74%) over alcoholic etiology. 21 As such gall stone disease was observed to be the most common etiology reported in different published reports similar to present study.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…20 However, Kumar et al in their study, similar to current study reported a dominance of gall stone disease (74%) over alcoholic etiology. 21 As such gall stone disease was observed to be the most common etiology reported in different published reports similar to present study.…”
Section: Discussionsupporting
confidence: 81%
“…20 In the study by Kumar et al mean duration of hospital stay was 6.98 days which is slightly higher than that in present study. 21 Lower duration of hospital stay in present study could be owing to the tertiary care status of our facility where most of the patients were referred from primary or secondary care facilities and duration of hospital stay mentioned in the study is only reflective of stay at reported facility.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations